Effectiveness of Using Artificial Intelligence Chatbox Integrated Case Method on Science Learning Outcomes of Basic Education Students - Afriza Media; Syofianti Engreini; Risda Amini; Yogi Dian Alfana (Jurnal Penelitian Pendidikan IPA, 2025)
Advances in artificial intelligence (AI) have been widely used in learning innovation. This study aims to determine the effectiveness of using AI chatboxes integrated with case method on the science learning outcomes of basic education students. This research is a quasi-experimental research with a pretest-posttest control group design, which allows to compare learning outcomes in both sample classes. Data collection was carried out through pretest and posttest tests to measure the improvement of learning outcomes, and analysis of research data using SPSS 22. The population used was basic education students at Padang State University. The results showed that the use of AI chatbox integrated case method was quite effective in improving science learning outcomes with the acquisition of n-gain in the experimental class of 0.62 with a moderate category. The results of hypothesis test analysis show the Sig value. 0.004 <0.05 so that Ha is accepted. These results prove that the use of AI chatboxes integrated with the case method is effective in improving the science learning outcomes of basic education students. This research shows that the innovative use of AI technology in learning can have a positive impact on student academic achievement, especially in the field of basic education.